Health care providers' attitudes towards transfer and transition in young persons with long term illness- a web-based survey - Carina Sparud-Lundin; Malin Berghammer; Philip Moons; Ewa-Lena Bratt (BMC, 2017)
Abstract Background Transition programs in health care for young persons with special health care needs aim to maximize lifelong functioning. Exploring health care professionals' perspective may increase the possibility of successful implementation of transition programs. The aim was to survey health care professionals' attitudes towards components and barriers on transition and transfer in young people with long-term medical conditions with special health care needs. Methods A cross-sectional web-based survey was sent by e-mail to 529 physicians and nurses in Swedish pediatric and adult outpatient clinics. Response rate was 38% (n = 201). The survey consisted of 59 questions regarding different aspects of components and barriers on transition and transfer. Descriptive statistics were computed to summarize demographic data and categorized responses. The Chi square test was used for comparison between proportions of categories. Results Most respondents agreed on the destinations of care for adolescents within their specialty. Age and psychosocial aspects such as maturity and family situations were considered the most important initiators for transfer. Joint meeting with the patient (82%); presence of a transition coordinator (76%) and a written individualized transfer plan (55%) were reported as important transition components. Pediatric care professionals found the absence of a transition coordinator to be more of a transition barrier than adult care professionals (p = 0.018) and also a more important transfer component (p = 0.017). Other barriers were lack of funding (45%) and limited clinical space (19%). Transition programs were more common in university hospitals than in regional hospitals (12% vs 2%, p = <0.001) as well as having a transition coordinator (12% vs 3%, p = 0.004). Conclusion The findings highlight a willingness to work on new transition strategies and provide direction for improvement, taking local transition components as well as potential barriers into consideration when implementing future transition programs. Some differences in attitudes towards transitional care remain among pediatric and adult care professionals.